Mobile sink-based data collection scheme for wireless sensor networks - Jian GUO; Li-juan SUN; Wen-jun XU; Ru-chuan WANG; Fu XIAO (Tongxin xuebao, 2012)
The issue of data collection in wireless sensor networks was studied.A mobile sink-based data collection scheme called DCSR was proposed.DCSR consisted of two phases.Firstly,a number of collection sites were selected according to the sensor distribution.And then a quantum genetic algorithm was performed to calculate the shortest loop across the sites.The sink node would travel along this loop periodically and collect data at each site.Theoretical analysis and simulation results show that DCSR has better performance and collects more data.